Climate Change and Possible Impacts on Travel and Tourism Sector - KC, Ritika; Giri, Ija; Khadka, Udhab Raj (Journal of Tourism and Himalayan Adventures, 2021)
Nepal is a diverse country with lowlands of Terai to the highest mountains attracting many tourists and visitors to make visits. So, the tourism in Nepal is primarily nature-based as tourists are mostly attracted by the spectacular landscapes, majestic mountains, glaciers, lakes, rivers and biodiversity across its diverse ecological gradient. Mountaineering, trekking, whitewater rafting and jungle safari tours are the main forms of nature-based tourism activities in our country. Climate change is affecting Nepal in a number of ways and the travel and tourism sector cannot remain untouched. Various studies on climate change shows increased weather uncertainties and extremities resulting into long dry period and intense rain during monsoon leading to increased water induced disasters like floods, inundation, landslides, cloudburst floods, and glacial lake outburst floods (GLOFs) which are projected to continue in future as well. This has affected natural landscapes, and Himalayas influencing every walk of life and livelihood options. Though the impacts of climate change can be observed in the whole world, poor country like Nepal is likely to suffer most due to limited resources to cope with and adapt to the effects of climate change. In this paper, an effort has been made to review the impact of climate change on the travel and tourism sector in Nepal through the study of previous literatures on climate changes.